Relationship between thunderstorm electrification and storm kinetics revealed by phased array weather radar. Issue 7 (10th April 2017) - Yoshida, S.; Adachi, T.; Kusunoki, K.; Hayashi, S.; Wu, T.; Ushio, T.; Yoshikawa, E.
Abstract: We examine 3‐D lightning location data and radar data obtained through multiple radar observation stations, including two X‐band phased array weather radars (PAWRs), in order to understand the relationship between thunderstorm electrification and storm kinetics. In an investigated convective cell, both intracloud (IC) and cloud‐to‐ground (CG) flash rates drastically change within 25 min. First, the IC flash rate shows a steep increase with a peak at 10 min −1, and then, the CG flash rate peaks 7 min afterward. During the increase phase of the IC flash rate, the radar observation indicates that the echo top height and updraft echo volume in the upper level increase. The upper positive charge regions removed by IC flashes are located in or near the updraft region at high altitudes. On the contrary, the IC flash rate decreases when the updraft at high altitudes weakens. The IC flash rate is well correlated with a proxy for updraft volume in 1 min interval comparison. These results indicate that the IC flash rate has a strong connection with updraft at high altitudes. The CG flash rate peaks when precipitation particles, probably involving graupel, from high altitudes arrive at approximately the −10°C isotherm level. We speculate that graupel from high altitudes might contribute to the initiations of CG flashes. We show an abrupt ascent of the upper positive charge region involved in IC flashes. PAWR observation results indicate that the updraft might have contributed to the ascent of the upper positive lightning charge region. Key Points: Relationship between storm electrification and kinetics is revealed by two phased array weather radars and 3‐D lightning mapper observation In an investigated convective cell, the IC flash rate is well correlated with a proxy for updraft volume in 1 min interval comparison Descent of graupel particles from high altitudes to midlevel altitude might have contributed in initiating CG flashes